Chronic Coronary Syndrome: Overcoming Clinical Practice Guidelines. The role of the COMPASS Strategy - Ynsaurriaga, Fernando A.; Barrios, Vivencio; Amaro, Marisol B.; Martí-Almor, Julio; Martínez, Juan G.; Duque, José A.A.; Ruiz-Ortiz, Martín; Vázquez-García, Rafael; Muñoz, Alfonso V. (Current Cardiology Reviews, 2021)
Current European guidelines on chronic coronary syndromes recommend the use of low-dose aspirin (or clopidogrel if intolerance or contraindication occurs) throughout life. However, as the risk of recurrent vascular events is high, particularly in some patients (i.e. diffuse multivessel coronary artery disease, diabetes, recurrent myocardial infarction, peripheral artery disease, or chronic kidney disease,…), these guidelines also consider that in those patients at moderate or high risk of ischemic events, but without a high bleeding risk, dual antithrombotic therapy should be considered. According to these guidelines, treatment options for dual antithrombotic therapy in combination with aspirin may include clopidogrel 75 mg/daily, prasugrel 10 mg/daily, ticagrelor 60 mg bid or rivaroxaban 2.5 mg bid. Remarkably, despite the results of the clinical trials that sustain these recommendations clearly diverge, guidelines do not differentiate between them. However, although all these drugs have demonstrated a significant reduction in major cardiovascular events in patients with stable atherosclerotic disease, only the addition of rivaroxaban has been associated with a reduction in cardiovascular and overall mortality in the secondary analysis. This may be related to the fact that the activation of platelets and factor X plays a key role in the development of atherothrombosis, and, consequently, both targets should be considered for the appropriate management of these patients.
Keywords: MACE